Barbara A. Barletta. The Sanctuary of Athena at Sounion. pp. 360, with col. and b/w ills. 2018. Princeton: American School of Classical Studies at Athens (Ancient Art and Architecture in Context 4). ISBN: 978-0-87661-967-4, hardcover £65. - Lohmann, Hans (Journal of Greek Archaeology, 2020)
The extensive and lavishly illustrated book by Barletta is partly based on an unpublished manuscript by H.A. Thompson, the former director of the Agora Excavations, and of W.B. Dinsmoor Jr., the architect of the excavation. It was first editorially revised by M. McAllister and finally Barletta assumed the task to publish it after her own intensive studies of the sanctuary and its remains. Because of her untimely death, she did not see the final publication which was provided meticulously by D. Scahill.